EVALUASI PEMANFAATAN PROGRAM JAMINAN KESEHATAN NASIONAL DI DESA KLEPU, CEPER, KLATEN - Febriana Dwi Utami; Sumantri .; Desi Ekawati (STIKES DUTAGAMA KLATEN, 2015)
Background: In the Basic Law Number 36 Year 2009 on Health affirmed that everyone has equal rights in access between resources in health and health services that are safe, quality, and affordable. Social Security Agency has been regulated by Law No. 24 of 2011 on the Social Security Agency (BPJS) consisting of BPJS Health and BPJS Employment, implementation starting from 1 January 2014. The program, hereinafter referred to as the National Health Insurance program (Permenkes RI No. 28, 2014). Objective: To evaluate the use of the National Health Insurance program in the village Klepu, Ceper, Klaten. Methods: This study uses research methods of evaluation (evaluation study) with a mixed methodedesign. The population in this study is the head of a family in the village of Klaten Ceper Klepu consists of 855 heads of families with a target population of the National Health Insurance program participants as much as 400 households obtained 200 samples using a sampling technique Simple Random Sampling models. Results: The evaluation of the use of the National Health Insurance program in the village Klepu, Ceper, Klaten with a value of 73% both categories. The membership of the National Health Insurance program with a value of 69% of participants Beneficiary Contribution (PBI). The use of the National Health Insurance program with a value of 100% pertained use. Barriers for implementation of the National Health Insurance program with a value of 92% is still classified as experiencing barriers for the implementation of the National Health Insurance program. Conclusions: The use of the National Health Insurance program with a value of 73% fall into either category.